2017
DOI: 10.1186/s12987-017-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Barrier dysfunction or drainage reduction: differentiating causes of CSF protein increase

Abstract: BackgroundCerebrospinal fluid (CSF) protein analysis is an important element in the diagnostic chain for various central nervous system (CNS) pathologies. Among multiple existing approaches to interpreting measured protein levels, the Reiber diagram is particularly robust with respect to physiologic inter-individual variability, as it uses multiple subject-specific anchoring values. Beyond reliable identification of abnormal protein levels, the Reiber diagram has the potential to elucidate their pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Convective mixing is perhaps better called dispersion [ 78 ]. Papisov [ 133 ] and Asgari et al [ 134 ] discuss a similar effect in the spinal cord allowing transport of solutes down their concentration gradients against the direction of net flow of CSF and at rates much greater than allowed by diffusion. In this proposal diffusion is taken to be adequate to explain movements within the interstitial spaces in the parenchyma because the distances involved are sufficiently short (see Sect.…”
Section: Perivascular Pathwaysmentioning
confidence: 99%
“…Convective mixing is perhaps better called dispersion [ 78 ]. Papisov [ 133 ] and Asgari et al [ 134 ] discuss a similar effect in the spinal cord allowing transport of solutes down their concentration gradients against the direction of net flow of CSF and at rates much greater than allowed by diffusion. In this proposal diffusion is taken to be adequate to explain movements within the interstitial spaces in the parenchyma because the distances involved are sufficiently short (see Sect.…”
Section: Perivascular Pathwaysmentioning
confidence: 99%
“…These include flow through arachnoid villi to spinal veins (Elman, 1923; Welch and Pollay, 1963; Kido et al, 1976), routes along spinal nerve roots to epidural lymphatics (Iwanow, 1928; Brierley and Field, 1948), and routes through the arachnoid layer of the spinal meninges to dural lymphatics (Zenker et al, 1994; Antila et al, 2017). Previous groups have estimated that 16–25% of total CSF outflow may occur from the spine (Marmarou et al, 1975; Bozanovic-Sosic et al, 2001; Asgari et al, 2017). Others have suggested that spinal outflow pathways to lymphatic vessels are not active under normal conditions and that pathways through the cranial outflow routes must be blocked and/or that CSF pressures need to be elevated to produce outflow (Miura et al, 1998; Voelz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, if the CSF protein concentration increases, it may indicate the progress of the disease, and timely treatment is necessary. As we know, reduction of CSF drainage from the cranio-spinal space, inflammation induced-protein production as well as BBB damage have been suggested as possible causes of increased concentration of CSF proteins [18].Our study showed that the QAlb in the symptomatic NS group was significantly higher than in the ANS group, suggesting that the BBB damage was more severe in the symptomatic NS group. This may explain why the symptomatic NS group had higher CSF protein.…”
Section: Discussionmentioning
confidence: 44%